Purification and Identification of Positive Regulators Binding to a Novel Element in the c-jun Promoter - Jiang, Daifeng (2008)
A putative response element, GAGCCTC, was observed years ago in foot-printing analysis of the c-jun promoter and here we investigate its function in regulating c-jun expression and identify a protein complex that binds there. Electrophoretic mobility shift assays demonstrate a sequence-specific binding complex with this element in HEK293 cells. Additionally, unlabeled consensus AP-1 element DNA, but not a similar NF-jun element DNA, competes with complex formation. Mutations of this element decrease c-jun promoter reporter activity by nearly 5-fold in HEK293 cells. A new, two-step oligonucleotide trapping technique was developed to purify the element binding proteins. LC-Nanospray-ESI-MS/MS identification and western blotting show that the purified complex contains Ku80, and c-jun, which was further confirmed by antibody supershift, by immunoprecipitation with southwestern blot or with UV crosslinking analysis in vitro as well as chromatin immunoprecipitation in vivo. c-Jun promoter activity and c-jun expression were decreased by Ku80 siRNA introduction. A mutant Ku80 plasmid with normal amino acid sequence but immune to the siRNA recovers c-jun promoter activity from siRNA inhibition. Similarly, Ku70 wild type transfection can also up-regulate c-jun promoter activity. Thus , Ku80-c-jun activates c-jun expression by binding to this GAGCCTC element in the c-jun promoter and Ku70 may also serve a role.